IMMU-28. INDUCTION OF TERTIARY LYMPHOID STRUCTURE-LIKE T-CELL CLUSTERS BY DELIVERY OF A NOVEL GENE COMBINATION INTO AN IMMUNOCOMPETENT MOUSE MODEL OF GLIOBLASTOMA. (9th November 2020) - Downey, Kira; Hegde, Bindu; Chheda, Zinal; Zhang, Jason; Okada, Hideho
Abstract: The lack of conventional lymphatic drainage to and from the brain parenchyma restricts the capacity of the peripheral immune system to recognize and respond to glioma antigens. In some peripheral solid tumor types and central nervous system autoimmunity, the spontaneous development of tertiary lymphoid structures (TLS) with varying degrees of organization have been observed in human patients and mice following chronic inflammation. In the cancer setting, presence of TLS are generally associated with improved prognosis, especially when they are characterized by intratumoral infiltration of CD8 + T-cells. We aimed to induce the development of TLS in vivo, utilizing our SB28 glioblastoma model which is sparsely infiltrated by lymphocytes. As a proof-of-concept study, we stably transduced SB28 with a combination of several TLS-stimulating factors that we've identified and injected these cells into the brain parenchyma of syngeneic C57BL/6J mice. A combination of the chemoattractant and lymphoid follicle-stimulating cytokines LIGHT, CCL21, IL-7, and IL-17 produced substantial infiltration of CD8 + CD3 + T-cells into the tumor and nearby parenchyma. However, this combination was also associated with accelerated tumor growth. A modified gene combination including LIGHT, CCL21, and IL-7 promoted CD8 + CD3 + T-cell infiltration by flow cytometry, T-cell clustering by immunofluorescence analysis, and inhibited tumor burden compared with the control as measured by bioluminescent imaging. There was also evidence of increased lymphatic vasculature around the margins of T-cell clustering as demonstrated by LYVE-1 staining. Together, these analyses highlight a role for these factors in stimulating the recruitment and clustering of T-cell to the glioblastoma microenvironment in a TLS-like phenomenon. Future studies will evaluate whether the recruitment of other lymphocytes and stromal cells to these TLS-like clusters can promote T-cell memory and persistence. Ultimately, we aim to provide these factors utilizing a gene delivery method that will prove translatable to the clinic and complementary to existing T-cell therapies.